Olefin-based polymer composition having good impact properties, stiffness and light transmission
Patent Information
- Application Number
- CN202580023675.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]常规TPO配方通常不适合用于半透明部件,因为它们所需的填料含量(例如,滑石含量>10重量%)导致不利着色的增加并且显著降低透光率
Smart Images

Figure CN123022744A_ABST
Abstract
Description
Background Technology
[0001] A recent trend in EV (electric vehicle) interior and exterior applications is the development of translucent TPO materials. These TPO materials can be easily separated / distinguished from other TPO materials and can also be used in safety-related applications such as LIDAR (Light Detection and Ranging) systems and ADAS (Advanced Driver Assistance Systems) mechanisms. These TPO materials are also used in automotive components such as bumper skins or interior door panels, to name a few. The requirements for TPO, especially for bumper skins, are excellent stiffness-hardness properties and outstanding diffuse light transmittance.
[0002] Conventional TPO formulations are generally unsuitable for translucent parts because the required filler content (e.g., talc content >10% by weight) leads to increased unfavorable coloring and significantly reduced light transmittance. Therefore, novel TPO compositions are needed that provide a good balance of impact resistance, stiffness, and light transmittance. Preferably, these compositions also maintain a stable neutral or white color.
[0003] International application PCT / US23 / 075387, filed on September 28, 2023, discloses a composition comprising a first composition containing at least the following components a and b: a) at least one ethylene / α-olefin multiblock interpolymer having a density ≥0.870 g / cc and a soft segment melt temperature (SS-Tm) ≤35°C, and b) a polymer composition containing at least one propylene homopolymer; wherein component a is present in an amount ≤50% by weight based on the weight of components a and b. See abstract. Such compositions exhibit excellent impact strength and light transmittance.
[0004] International publication WO 2022 / 258218 discloses a cover for a light source comprising a polyolefin composition comprising the following components: (A) 50% to 80% by weight of a propylene polymer comprising, by weight, at most and including 40% by weight of an α-olefin derived from ethylene and / or at least one of the formula CH2=CHR1, wherein R1 is a linear or branched C2-C8 alkyl; (B) 15% to 35% by weight of an elastomer component selected from the group consisting of: (B1) a copolymer of ethylene with at least one of the formula CH2=CHR2, wherein R2 is a linear or branched C1-C8 alkyl, (B2) a saturated or unsaturated styrene or α-methylstyrene block copolymer, and (B3) combinations thereof; (C) 5% to 30% by weight of glass fiber, and (D) 0% to 5.0% by weight of a compatibilizer. The amounts of (A), (B), (C), and (D) are based on the total weight of (A) + (B) + (C) + (D), which is 100% of the total weight. See the abstract. The propylene polymer (A) may be, for example, a propylene random copolymer, a polyolefin composition comprising a propylene random copolymer, or a heterogeneous propylene polymer comprising a crystalline or semi-crystalline matrix phase and a rubber phase dispersed therein (see paragraph
[0033] ).
[0005] U.S. Patent 8,921,491 discloses an impact-modified composition comprising an ethylene / α-olefin interpolymer. This ethylene / α-olefin interpolymer is characterized by an average block index (ABI) greater than zero and at most about 1.0, and a molecular weight distribution (Mw / Mn) greater than about 1.3. Furthermore, or alternatively, the block ethylene / α-olefin interpolymer is characterized by having at least one fraction obtained by heated rinsing fractionation (“TREF”), wherein the fraction has a block index greater than about 0.3 and at most about 1.0, and the ethylene / α-olefin interpolymer has a molecular weight distribution (Mw / Mn) greater than about 1.4. See abstract. Exemplary polymers for blending include polypropylene (impact-modified polypropylene, isotactic polypropylene, atactic polypropylene, and atactic ethylene / propylene copolymers), various types of polyethylene including high-pressure free radical LDPE, Ziegler-Natta LLDPE, metallocene PE, including multi-reactor PE (“in-reactor blends of Ziegler-Natta PE and metallocene PE, such as the products disclosed in U.S. Patent Nos. 6,545,088, 6,538,070, 6,566,446, 5,844,045, 5,869,575, and 6,448,341”), ethylene-vinyl acetate (EVA), ethylene / ethylene Alcohol copolymers, polystyrene, impact-modified polystyrene, acrylonitrile-butadiene-styrene (ABS), styrene / butadiene block copolymers and their hydrogenated derivatives (SBS and SEBS), polyisobutylene (PIB) homopolymers, PIB-isoprene copolymers, EPDM, and thermoplastic polyurethanes (see column 32, rows 32–45). The “soft segment Tm (°C) from weighted DSC” for several polymers is listed in Table 16 (see column 72, rows 6–29). For compositions containing propylene homopolymers, see, for example, Table 27 (column 81) and Table 32 (column 85). See also Table 43 (column 89).
[0006] U.S. Patent 7,893,166 discloses a class of ethylene / α-olefin block copolymers characterized by an average block index (ABI) greater than zero and at most about 1.0 and a molecular weight distribution (MWD) greater than about 1.3. Preferably, the block index is from about 0.2 to about 1. Furthermore, or alternatively, the block ethylene / α-olefin copolymers are characterized by having at least one fraction obtained by heated wash fractionation (TREF), wherein the fraction has a block index greater than about 0.3 and at most about 1.0, and the ethylene / α-olefin copolymer has a molecular weight distribution greater than about 1.3 (see abstract). The “soft segment Tm (°C) values from weighted DSC” for several polymers are listed in Table 16 (see column 60, lines 11-35). This patent discloses polymers for blending, including polypropylene (see, for example, column 25, lines 11-33). See also U.S. Patent 7,608,668.
[0007] Additional compositions and / or components (such as automotive parts) are described in the following references: U.S. Patent 10,557,005, U.S. Patent 7,947,793, U.S. Patent 8,084,537, U.S. Patent 7,592,397, U.S. Patent 7,863,379, U.S. Patent 8,573,665, U.S. Patent 5,925,703, U.S. Patent 8,455,087, U.S. Patent 7,741,397, U.S. Patent Publication 2015 / 0291085, U.S. Patent Publication 2012 / 0313392, International Publication WO2014 / 036292, and GB2552996A.
[0008] However, as discussed above, there remains a need for novel TPO compositions that can provide a good balance between impact performance, stiffness, and light transmittance. This need is met as discussed below. Summary of the Invention
[0009] A composition comprising a first composition, the first composition comprising at least the following components a and b:
[0010] a) at least one ethylene / α-olefin multiblock interpolymer, and
[0011] b) At least one propylene-based polymer having a molecular weight distribution (MWD) ≤ 5.0. Attached Figure Description
[0012] Figure 1 The DSC curves (second heating curves) of METOCENE HM648T (upper curve at 100°C), BRASKEM D115A (intermediate curve at 100°C), and BRASKEM F1000HC (lower curve at 100°C) are shown.
[0013] Figure 2 The "enthalpy of melting (J / g) versus temperature (°C)" of the linear copolymers described herein is depicted. Detailed Implementation
[0014] TPO compositions have been discovered that offer a good balance of impact resistance, stiffness, and light transmittance. As discussed above, a composition is provided comprising a first composition comprising at least the following components a and b: a) at least one ethylene / α-olefin multiblock interpolymer, and b) at least one propylene-based polymer having a molecular weight distribution (MWD) ≤ 5.0. The above composition may comprise a combination of two or more embodiments as described herein. The first composition may comprise a combination of two or more embodiments as described herein. Each component a and b may independently comprise a combination of two or more embodiments as described herein.
[0015] In one embodiment, or in a combination of two or more embodiments each described herein, the MWD of at least one propylene-based polymer of component b is ≤4.9, or ≤4.8, or ≤4.7, or ≤4.6, or ≤4.5.
[0016] In one embodiment, or in a combination of two or more embodiments each described herein, the MWD of at least one propylene-based polymer of component b is ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.2, or ≥3.4, or ≥3.6, or ≥3.8, or ≥4.0.
[0017] In one embodiment, or in a combination of two or more embodiments each described herein, at least one propylene-based polymer of component b has a T m1 ≤160℃, or ≤158℃, or ≤156℃, or ≤154℃, or ≤152℃, or ≤150℃, or ≤149℃, or ≤148℃. Note that T m1 Refer to the secondary heating curve in the DSC analysis described herein, and if the secondary heating curve has two or more melting peaks, this refers to the highest peak temperature. See, for example... Figure 1 .
[0018] In one embodiment, or in a combination of two or more embodiments each described herein, the T of the at least one propylene-based polymer of component b m1 ≥130℃, or ≥132℃, or ≥134℃, or ≥136℃, or ≥138℃, or ≥139℃, or ≥140℃, or ≥141℃, or ≥142℃, or ≥143℃, or ≥144℃.
[0019] In one embodiment, or in a combination of two or more embodiments described herein, at least one propylene-based polymer of component b has T m2 And among them (T) m1– 11.0℃) ≤ T m2 ≤ (T m1 – 5.0℃). Note that if the second heating curve has two or more melting peaks, then T m2 This refers to the second peak temperature. See, for example... Figure 1 .
[0020] In one embodiment, or in a combination of two or more embodiments described herein, at least one propylene-based polymer of component b is a propylene homopolymer.
[0021] In one embodiment, or in a combination of two or more embodiments described herein, component b comprises a propylene-based polymer, and more particularly a propylene homopolymer.
[0022] In one embodiment, or in a combination of two or more embodiments described herein, component b comprises two propylene-based polymers, and further two propylene homopolymers.
[0023] In one embodiment, or in a combination of two or more embodiments described herein, the density of at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥0.870 g / cc, or ≥0.871 g / cc, or ≥0.872 g / cc, or ≥0.873 g / cc, or ≥0.874 g / cc, or ≥0.875 g / cc, or ≥0.876 g / cc, or ≥0.877 g / cc, or ≥0.878 g / cc, or ≥0.879 g / cc, or ≥0.880 g / cc, or ≥0.881 g / cc, or ≥0.882 g / cc, or ≥0.883 g / cc, or ≥0.884 g / cc. In one embodiment, or in a combination of two or more embodiments described herein, the density of at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≤0.910 g / cc, or ≤0.908 g / cc, or ≤0.906 g / cc, or ≤0.904 g / cc, or ≤0.902 g / cc, or ≤0.900 g / cc, or ≤0.898 g / cc, or ≤0.896 g / cc, or ≤0.894 g / cc, or ≤0.892 g / cc, or ≤0.890 g / cc, or ≤0.889 g / cc, or ≤0.888 g / cc, or ≤0.887 g / cc.
[0024] In one embodiment, or in a combination of two or more embodiments described herein, the SS-Tm of at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≤35°C, or ≤30°C, or ≤25°C, or ≤20°C, or ≤18°C, or ≤16°C, or ≤14°C, or ≤12°C, or ≤10°C, or ≤9°C, or ≤8°C, or ≤7°C, or ≤6°C. In one embodiment, or in a combination of two or more embodiments described herein, the SS-Tm of at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥-20°C, or ≥-18°C, or ≥-16°C, or ≥-14°C, or ≥-12°C, or ≥-10°C, or ≥-8°C, or ≥-6°C, or ≥-4°C, or ≥-2°C, or ≥-1°C, or ≥0°C, or ≥1°C, or ≥2°C, or ≥3°C, or ≥4°C.
[0025] In one embodiment, or in a combination of two or more embodiments described herein, the melt index (MI or I2) of at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥0.10 g / 10 min, or ≥0.20 g / 10 min, or ≥0.40 g / 10 min, or ≥0.60 g / 10 min, or ≥0.80 g / 10 min, or ≥1.0 g / 10 min, or ≥2.0 g / 10 min. And / or ≤50g / 10min, or ≤45g / 10min, or ≤40g / 10min, or ≤35g / 10min, or ≤30g / 10min, or ≤28g / 10min, or ≤26g / 10min, or ≤24g / 10min, or ≤22g / 10min, or ≤20g / 10min, or ≤18g / 10min, or ≤16g / 10min, or ≤14g / 10min, or ≤12g / 10min, or ≤10g / 10min, or ≤9.0g / 10min, or ≤8.0g / 10min, or ≤7.0g / 10min, or ≤6.0g / 10min, or ≤5.0g / 10min.
[0026] In one embodiment, or in a combination of two or more embodiments described herein, the first composition further comprises at least one ethylene / α-olefin interpolymer as component c, and further at least one ethylene / α-olefin copolymer.
[0027] In one embodiment, or in a combination of two or more embodiments described herein, at least one ethylene / α-olefin interpolymer (of component c) is a random ethylene / α-olefin interpolymer.
[0028] In one embodiment, or in a combination of two or more embodiments described herein, the weight ratio of component a to component c is ≥1.2, or ≥1.5, or ≥1.8, or ≥2.0, or ≥2.2, or ≥2.4. And / or ≤4.0, or ≤3.8, or ≤3.5, or ≤3.2, or ≤3.0, or ≤2.8, or ≤2.6.
[0029] In one embodiment, or in a combination of two or more embodiments described herein, the weight ratio of component b to component a is ≥1.1, or ≥1.2, or ≥1.4, or ≥1.6, or ≥1.8. And / or ≤6.0, or ≤5.8, or ≤5.5, or ≤5.2, or ≤5.0, or ≤4.8, or ≤4.5, or ≤4.2, or ≤4.0, or ≤3.8, or ≤3.5, or ≤3.2, or ≤3.0, or ≤2.8, or ≤2.6, or ≤2.5.
[0030] In one embodiment, or in a combination of two or more embodiments described herein, the composition further comprises at least one filler. In one embodiment, or in a combination of two or more embodiments described herein, the at least one filler is selected from talc, nanoclay, or combinations thereof, and further selected from talc.
[0031] In one embodiment, or in a combination of two or more embodiments each described herein, the composition has an MFR ≥ 5.0 g / 10 min, or ≥ 7.0 g / 10 min, or ≥ 10 g / 10 min, or ≥ 12 g / 10 min, or ≥ 15 g / 10 min, or ≥ 18 g / 10 min, or ≥ 20 g / 10 min, or ≥ 22 g / 10 min, or ≥ 24 g / 10 min, or ≥ 26 g / 10 min. and And / or ≤100g / 10min, or ≤80g / 10min, or ≤60g / 10min, or ≤50g / 10min, or ≤48g / 10min, or ≤45g / 10min, or ≤42g / 10min, or ≤40g / 10min, or ≤38g / 10min, or ≤36g / 10min, or ≤34g / 10min, or ≤32g / 10min.
[0032] In one embodiment, or in a combination of two or more embodiments described herein, the composition has a light transmittance (3.2 mm thickness) at room temperature (23°C) of ≥30%, ≥35%, ≥40%, ≥45%, ≥50%, ≥55%, or ≥60%. And / or ≤100%, or ≤95%. Transmittance was measured as described in this article.
[0033] In one embodiment, or in a combination of two or more embodiments described herein, the composition exhibits a dart-drop ductility of ≥70%, ≥75%, ≥80%, ≥85%, ≥90%, ≥95%, or 100% at -30°C (6.6 m / s).
[0034] In one embodiment, or in a combination of two or more embodiments described herein, the composition has a Charpy impact of ≥400 J / m, or ≥410 J / m, or ≥420 J / m, or ≥430 J / m, or ≥440 J / m, or ≥450 J / m, or ≥460 J / m, or ≥470 J / m, or ≥480 J / m, or ≥490 J / m, or ≥500 J / m at 23°C (room temperature).
[0035] In one embodiment, or in a combination of two or more embodiments described herein, the composition has a flexural modulus of ≥80 ksi, or ≥85 ksi, or ≥90 ksi, or ≥95 ksi, or ≥100 ksi, or ≥105 ksi, or ≥110 ksi.
[0036] An article of manufacture is also provided, comprising at least one component formed of a composition of one embodiment or a combination of two or more embodiments described herein. In another embodiment, the article of manufacture is an automotive component.
[0037] A method for forming an article is also provided, the method comprising mixing a composition of one embodiment or a combination of two or more embodiments described herein.
[0038] Ethylene / α-olefin multiblock interpolymer
[0039] Ethylene / α-olefin multiblock interpolymers and copolymers comprise ethylene and α-olefins in polymeric form. α-olefins include, but are not limited to, C3-C20 α-olefins, further C3-C10 α-olefins, further C3-C8 α-olefins, such as propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene.
[0040] Ethylene / α-olefin multiblock interpolymers are characterized by multiple blocks or segments of two or more polymerizable monomer units, which have different chemical or physical properties. In some embodiments, the multiblock interpolymer and further copolymers can be represented by the formula (AB)n, where n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or greater. In this document, “A” represents a hard block or segment, and “B” represents a soft block or segment. Preferably, segments A and B are connected (or covalently bonded) in a substantially linear manner, contrary to a substantially branched or substantially star-shaped manner. In other embodiments, segments A and B are randomly distributed along the polymer chain. In other words, for example, the block interpolymer typically does not have a structure like AAA-AA-BBB-BB. In other embodiments, the block interpolymer typically does not have a third type of block or segment comprising one or more different comonomers. In still other embodiments, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B contains two or more sub-segments (or sub-blocks) of different compositions, such as end segments, having compositions substantially different from the rest of the block.
[0041] As used herein, the term "hard segment (HS)" refers to a block of polymerized monomer units, wherein ethylene is present in an amount, for example, >90 mol%, or ≥92 mol%, or ≥95 mol%, or ≥98 mol%, or ≥99 mol%, based on the total molar number of monomers polymerized in the block. In one embodiment, ethylene is present in an amount ≤99.8 mol%, or ≤99.6 mol%, or ≤99.4 mol%, or ≤99.3 mol%, based on the total molar number of monomers polymerized in the block.
[0042] As used herein, the term "soft segment (SS)" refers to a block of polymerized monomer units, wherein ethylene is present in an amount, for example, ≤90 mol%, or ≤88 mol%, or ≤86 mol%, or ≤84 mol%, or ≤82 mol%, based on the total molar number of monomers polymerized in the block. In one embodiment, ethylene is present in an amount ≥60 mol%, or ≥65 mol%, or ≥70 mol%, or ≥75 mol%, or ≥80 mol%, based on the total molar number of monomers polymerized in the block.
[0043] Soft segments may be present in ethylene / octene multiblock copolymers at 1 wt%, or 5 wt%, or 10 wt%, or 15 wt%, or 20 wt%, or 25 wt%, or 30 wt%, or 35 wt%, or 40 wt%, or 45 wt% to 50 wt%, or 55 wt%, or 60 wt%, or 65 wt%, or 70 wt%, or 75 wt%, or 80 wt%, or 85 wt%, or 90 wt%, or 95 wt%, or 99 wt% of the total weight of the copolymer. Conversely, hard segments may be present in a similar range. The weight percentages of soft and hard segments can be calculated based on data obtained from DSC or NMR. Such methods and calculations are disclosed, for example, in USP 7,608,668, the disclosure of which is incorporated herein by reference in its entirety. For example, the weight percentages of hard and soft segments can be determined as described in columns 57 through 63 of U.S. Patent 7,608,668, which is incorporated herein by reference.
[0044] Typically, ethylene comprises 50 mole percent or the majority mole percent of the entire multiblock interpolymer; that is, ethylene comprises at least 50 mole percent of the entire interpolymer. More preferably, ethylene comprises at least 60 mole percent, or at least 70 mole percent, or at least 80 mole percent, or at least 90 mole percent, while the substantially remaining portion of the entire polymer contains at least one other comonomer, which is preferably an α-olefin having three or more carbon atoms.
[0045] As discussed, ethylene / α-olefin multiblock interpolymers comprise two or more chemically distinct regions or segments (referred to as “blocks”), preferably connected in a linear manner. In one embodiment, the blocks differ in the amount or type of comonomers incorporated, density, amount of crystallinity, crystallite size of the polymer attributable to the composition, type or degree of stereoisomerism (isosterolactic or synisosterol), regioregularity or regioirorality, amount of branching (including long-chain branching or hyperbranching), homogeneity, or any other chemical or physical property. Compared to prior art block interpolymers (including interpolymers produced by sequential monomer addition, dynamic catalysts, or anionic polymerization techniques), the ethylene / α-olefin multiblock interpolymers of the present invention are characterized by a unique distribution of polymer polydispersity (PDI or Mw / Mn or MWD), polydisperse block length distribution, and / or polydisperse block number distribution, which in one embodiment is attributed to the combined effect of the shuttle agent used in its preparation with multiple catalysts.
[0046] Ethylene / α-olefin multiblock interpolymers and further copolymers can generally be produced via chain shuttle methods, such as those described, for example, in U.S. Patent 7,858,706, which is incorporated herein by reference. Some chain shuttles and related information are listed in column 16, line 39 through column 19, line 44. Some catalysts are described in column 19, line 45 through column 46, line 19, and some co-catalysts are described in column 46, line 20 through column 51, line 28. Some process features are described in column 51, line 29 through column 54, line 56. See also: U.S. Patent 7,608,668; U.S. Patent 7,893,166; and U.S. Patent 7,947,793 and U.S. Patent 8,476,393. See also U.S. Patent 9,243,173.
[0047] In one embodiment, the ethylene / α-olefin multiblock copolymer (e.g., ethylene / octene multiblock copolymer) is produced by a continuous method and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When prepared by a batch or semi-batch method, the ethylene / α-olefin multiblock copolymer (e.g., ethylene / octene multiblock copolymer) typically has a Mw / Mn of 1.0 to 3.5, or 1.3 to 3.0, or 1.4 to 2.5, or 1.4 to 2.0.
[0048] Furthermore, ethylene / α-olefin polyblock interpolymers (e.g., ethylene / octene polyblock interpolymers) typically have a PDI (or Mw / Mn) that fits a Schultz-Flory distribution rather than a Poisson distribution. In one embodiment, the ethylene / α-olefin polyblock interpolymer (e.g., ethylene / octene polyblock interpolymer) has both a polydisperse block distribution and a polydisperse block size distribution. This results in the formation of polymer products with improved and distinguishable physical properties. The theoretical benefits of polydisperse block distribution have previously been modeled and discussed in Potemkin, Physical Review E (1998) 57 (6), pp. 6902–6912 and Dobrynin, J. Chem. Phys. (1997) 107 (21), pp. 9234–9238. In one embodiment, ethylene / α-olefin multiblock interpolymers (such as ethylene / octene multiblock interpolymers) have the most probable distribution of block lengths.
[0049] definition
[0050] Unless stated to the contrary, implied by the context or customary in the art, all parts and percentages are by weight, and all test methods are current methods as of the date of this disclosure.
[0051] As used herein, the term "composition" includes a mixture of materials constituting the composition, as well as reaction products and decomposition products formed from the materials of the composition. Any reaction product or decomposition product is typically present in trace or residual amounts.
[0052] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Therefore, the general term polymer includes the terms homopolymer (used to refer to polymers prepared from only one type of monomer; it should be understood that trace impurities may be incorporated into the polymer structure) and interpolymer as defined below. Trace impurities (such as catalyst residues) may be incorporated into and / or within the polymer. Typically, polymers are stabilized with very low amounts ("ppm") of one or more stabilizers, such as one or more antioxidants.
[0053] As used herein, the term "interpolymer" refers to a polymer prepared by the polymerization of at least two different types of monomers. The term interpolymer therefore includes the term copolymer (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0054] As used herein, the term "olefin-based polymer" refers to a polymer that contains 50% by weight or most of a weight of an olefin (such as ethylene or propylene) in polymeric form (by weight of the polymer) and may optionally contain one or more comonomers.
[0055] As used herein, the term "propylene-based polymer" refers to a polymer that contains a majority weight percentage of propylene (by weight of the polymer) in polymeric form and may optionally contain one or more comonomers.
[0056] As used herein, the term "ethylene-based polymer" refers to a polymer that contains 50% by weight or most of the weight of ethylene (based on the weight of the polymer) in polymeric form and optionally may contain one or more comonomers.
[0057] As used herein, the term "ethylene / α-olefin interpolymer" refers to an interpolymer comprising 50% by weight or a majority by weight of ethylene (based on the weight of the interpolymer) and α-olefin in polymeric form. The term "ethylene / α-olefin interpolymer" does not include "ethylene / α-olefin multiblock interpolymers" as described herein. Preferably, "ethylene / α-olefin interpolymer" is a random "ethylene / α-olefin interpolymer"—that is, the α-olefin is randomly distributed within the interpolymer.
[0058] As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer in polymeric form comprising 50% by weight or the majority of ethylene (based on the weight of the copolymer) and α-olefin as the only two monomer types. The term "ethylene / α-olefin copolymer" does not include "ethylene / α-olefin multiblock copolymer" as described herein. Preferably, "ethylene / α-olefin copolymer" is a random "ethylene / α-olefin copolymer"—that is, α-olefin is randomly distributed within the copolymer.
[0059] As used herein, the term "ethylene / α-olefin multiblock interpolymer" refers to a multiblock interpolymer comprising, in polymeric form, 45% by weight, and further 50% by weight or majority by weight of ethylene (based on the weight of the interpolymer) and α-olefin. As used herein, the term "ethylene / α-olefin multiblock copolymer" refers to a multiblock copolymer comprising, in polymeric form, 45% by weight, and further 50% by weight or majority by weight of ethylene (based on the weight of the copolymer) and α-olefin as the only two monomer types. See also the previous discussion.
[0060] As used herein, the term "propylene homopolymer or polypropylene homopolymer" refers to a homopolymer that contains propylene as a monomer in a polymeric form.
[0061] As used herein, the term "propylene / α-olefin interpolymer" refers to an interpolymer comprising, in polymeric form, a majority weight percentage of propylene (based on the weight of the interpolymer) and an α-olefin. Preferably, a "propylene / α-olefin interpolymer" is a random "propylene / α-olefin interpolymer"—that is, the α-olefin is randomly distributed within the interpolymer.
[0062] As used herein, the term "propylene / α-olefin copolymer" refers to a copolymer in which the majority of the monomers (based on the weight of the copolymer) and α-olefins are the only two monomer types in a polymeric form. Preferably, a "propylene / α-olefin copolymer" is a random "propylene / α-olefin copolymer"—that is, the α-olefins are randomly distributed within the copolymer.
[0063] As used herein, the term "propylene / ethylene interpolymer" refers to an interpolymer comprising, in polymeric form, a majority weight percentage of propylene (based on the weight of the interpolymer) and ethylene. Preferably, a "propylene / ethylene interpolymer" is a random "propylene / ethylene interpolymer"—that is, ethylene is randomly distributed within the interpolymer.
[0064] As used herein, the term "propylene / ethylene copolymer" refers to a copolymer in which the majority of the monomers (based on the weight of the copolymer) and ethylene are the only two monomer types in a polymeric form. Preferably, a "propylene / ethylene copolymer" is a random "propylene / ethylene copolymer"—that is, ethylene is randomly distributed within the copolymer.
[0065] As used herein, the phrase “major weight percentage” for polymers (or interpolymers or copolymers) refers to the amount of monomers present in the polymer in the largest quantity.
[0066] As used herein, the term "antistatic agent" refers to a compound used to treat a material or its surface in order to reduce or eliminate static electricity buildup. Commercially available antistatic agents are typically based on imidazoline, pyridinium, piperidinium, and morpholinium salts.
[0067] As used herein, the term "nucleating agent" generally refers to a compound used to induce the formation of polymer crystals. Examples include, but are not limited to, talc, sodium benzoate, phosphate esters, and other organic salts.
[0068] As used herein, the terms “heat-treated,” “heat-processed,” and similar phrases relating to compositions described herein refer to raising the temperature of the composition by applying heat. As an example, heat can be applied by electrical components (e.g., heating coils) and / or by radiation and / or by hot oil and / or by mechanical shearing. Note that the temperature at which heat treatment is performed refers to the temperature of the apparatus “applying heat,” or, if the apparatus contains a closed or semi-closed atmosphere, the temperature of the atmosphere within the apparatus, such as the atmosphere in an oven or tunnel (e.g., the air temperature in a hot air oven or hot air tunnel).
[0069] The terms “comprising,” “including,” “having,” and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, unless stated to the contrary, all compositions claimed using the term “comprising” may include, for example, any additional additives, adjuvants, or compounds, whether polymerized or otherwise. In contrast, the term “consistently comprising” excludes any other components, steps, or procedures from any subsequently listed scope, except those not essential for operability. The term “consisting of” excludes any ingredients, steps, or procedures not specifically described or listed.
[0070] List of some composition characteristics
[0071] A] A composition comprising a first composition, the first composition comprising at least the following components a and b:
[0072] a) at least one ethylene / α-olefin multiblock interpolymer, and
[0073] b) At least one propylene-based polymer, wherein the MWD of the propylene-based polymer is ≤5.0.
[0074] B] The composition according to A] wherein the MWD of the at least one propylene-based polymer of component b is ≤4.9, or ≤4.8, or ≤4.7, or ≤4.6, or ≤4.5.
[0075] C] The composition according to A] or B] wherein the MWD of the at least one propylene-based polymer of component b is ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.2, or ≥3.4, or ≥3.6, or ≥3.8, or ≥4.0.
[0076] D] The composition according to any one of A]-C] (A] to C], wherein the T of the at least one propylene-based polymer of component b m1 ≤160℃, or ≤158℃, or ≤156℃, or ≤154℃, or ≤152℃, or ≤150℃, or ≤149℃, or ≤148℃.
[0077] Note that T m1 Refer to the secondary heating curve in the DSC analysis described herein, and if the secondary heating curve has two or more melting peaks, this refers to the highest peak temperature. See, for example... Figure 1 .
[0078] E] The composition according to any one of A]-D], wherein the T of the at least one propylene-based polymer of component b m1 ≥130℃, or ≥132℃, or ≥134℃, or ≥136℃, or ≥138℃, or ≥139℃, or ≥140℃, or ≥141℃, or ≥142℃, or ≥143℃, or ≥144℃.
[0079] Note that if the second heating curve has two or more melting peaks, then T m2 This refers to the second peak temperature. See, for example... Figure 1 .
[0080] F] The composition according to any one of A]-E], wherein the at least one propylene-based polymer of component b has T m2 And among them (T) m1 – 11.0℃) ≤ T m2 ≤ (T m1 – 5.0℃).
[0081] G] The composition according to any one of A]-F], wherein the crystallinity of the at least one propylene-based polymer of component b is ≤75%, or ≤73%, or ≤71%, or ≤70%, or ≤69%, or ≤68%, or ≤67%, or ≤66%.
[0082] H] The composition according to any one of A]-G], wherein the crystallinity of the at least one propylene-based polymer of component b is ≥50%, or ≥52%, or ≥55%, or ≥56%, or ≥57%, or ≥58%, or ≥59%, or ≥60%, or ≥61%, or ≥62%, or ≥63%, or ≥64%.
[0083] I] The composition according to any one of A]-H], wherein the at least one propylene-based polymer of component b is a propylene homopolymer.
[0084] J] The composition according to any one of A]-H], wherein the at least one propylene-based polymer of component b is a propylene / ethylene interpolymer, and further is a propylene / ethylene copolymer. Further, the propylene / ethylene interpolymer or copolymer is a random interpolymer or random copolymer.
[0085] K] The composition according to any one of A]-H], wherein the at least one propylene-based polymer of component b is a propylene / α-olefin interpolymer, and further is a propylene / olefin-olefin copolymer. Further, the propylene / α-olefin interpolymer or copolymer is a random interpolymer or random copolymer.
[0086] L] According to the composition described in K] above, wherein the α-olefin of the propylene / α-olefin interpolymer and further copolymer is a C4-C20 α-olefin, further a C4-C10 α-olefin, and further a C4-C8 α-olefin.
[0087] M] According to the composition described in K] or L] above, wherein the α-olefin is selected from 1-butene, 1-pentene, 1-hexene or 1-octene, and further is 1-butene or 1-octene, and further is 1-octene.
[0088] N] The composition according to any one of A]-M] above, wherein the melt flow rate (MFR) of the at least one propylene-based polymer (of component b) is ≥1.0 g / 10 min, or ≥2.0 g / 10 min, or ≥3.0 g / 10 min, or ≥4.0 g / 10 min, or ≥5.0 g / 10 min, or ≥10 g / 10 min, or ≥20 g / 10 min, or ≥25 g / 10 min, or ≥30 g / 10 min, or ≥35 g / 10 min, or ≥40 g / 10 min, or ≥45 g / 10 min, or ≥50 g / 10 min, or ≥55 g / 10 min.
[0089] O] The composition according to any one of A]-N] above, wherein the melt flow rate (MFR) of the at least one propylene-based polymer (of component b) is ≤200 g / 10 min, or ≤150 g / 10 min, or ≤100 g / 10 min, or ≤90 g / 10 min, or ≤80 g / 10 min, or ≤75 g / 10 min, or ≤70 g / 10 min, or ≤65 g / 10 min.
[0090] [P] The composition according to any one of A]-O] above, wherein the density of the at least one propylene-based polymer (of component b) is ≥0.875 g / cc, or ≥0.880 g / cc, or ≥0.885 g / cc, or ≥0.890 g / cc, or ≥0.895 g / cc, or ≥0.900 g / cc (1 g / cc = 1 g / cm³). 3 ).
[0091] Q] The composition according to any one of A]-P] above, wherein the density of the at least one propylene-based polymer (of component b) is ≤0.935 g / cc, or ≤0.930 g / cc, or ≤0.925 g / cc, or ≤0.920 g / cc, or ≤0.915 g / cc, or ≤0.910 g / cc, or ≤0.905 g / cc.
[0092] R] The composition according to any one of A]-Q] above, wherein component b comprises two propylene-based polymers, and further two propylene homopolymers.
[0093] S] The composition according to any one of A]-Q] above, wherein component b comprises a propylene-based polymer, and further a propylene homopolymer.
[0094] [T] The composition according to any one of A]-S] above, wherein the density of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥0.870 g / cc, or ≥0.871 g / cc, or ≥0.872 g / cc, or ≥0.873 g / cc, or ≥0.874 g / cc, or ≥0.875 g / cc, or ≥0.876 g / cc, or ≥0.877 g / cc, or ≥0.878 g / cc, or ≥0.879 g / cc, or ≥0.880 g / cc, or ≥0.881 g / cc, or ≥0.882 g / cc, or ≥0.883 g / cc, or ≥0.884 g / cc.
[0095] U] The composition according to any one of A]-T] above, wherein the density of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≤0.910 g / cc, or ≤0.908 g / cc, or ≤0.906 g / cc, or ≤0.904 g / cc, or ≤0.902 g / cc, or ≤0.900 g / cc, or ≤0.898 g / cc, or ≤0.896 g / cc, or ≤0.894 g / cc, or ≤0.892 g / cc, or ≤0.890 g / cc, or ≤0.889 g / cc, or ≤0.888 g / cc, or ≤0.887 g / cc.
[0096] V] The composition according to any one of A]-U] above, wherein the SS-Tm of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≤35°C, or ≤30°C, or ≤25°C, or ≤20°C, or ≤18°C, or ≤16°C, or ≤14°C, or ≤12°C, or ≤10°C, or ≤9°C, or ≤8°C, or ≤7°C, or ≤6°C.
[0097] W] The composition according to any one of A]-V] above, wherein the SS-Tm of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥-20°C, or ≥-18°C, or ≥-16°C, or ≥-14°C, or ≥-12°C, or ≥-10°C, or ≥-8°C, or ≥-6°C, or ≥-4°C, or ≥-2°C, or ≥-1°C, or ≥0°C, or ≥1°C, or ≥2°C, or ≥3°C, or ≥4°C.
[0098] X] The composition according to any one of A]-W] above, wherein the at least one ethylene / α-olefin multiblock interpolymer (of component a) is at least one ethylene / α-olefin multiblock copolymer.
[0099] Y] The composition according to any one of A]-X] above, wherein the α-olefin of the at least one ethylene / α-olefin multiblock interpolymer and further copolymer is a C3-C20 α-olefin, and further a C3-C10 α-olefin, and further a C3-C8 α-olefin.
[0100] Z] The composition according to any one of A]-Y] above, wherein the α-olefin of the at least one ethylene / α-olefin multiblock interpolymer and further copolymer is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further is propylene, 1-butene or 1-octene, and further is propylene or 1-octene, and further is 1-octene.
[0101] A2] The composition according to any one of A]-Z] above, wherein the melt index (MI or I2) of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥0.10 g / 10 min, or ≥0.20 g / 10 min, or ≥0.40 g / 10 min, or ≥0.60 g / 10 min, or ≥0.80 g / 10 min, or ≥1.0 g / 10 min, or ≥2.0 g / 10 min And / or ≤50g / 10min, or ≤45g / 10min, or ≤40g / 10min, or ≤35g / 10min, or ≤30g / 10min, or ≤28g / 10min, or ≤26g / 10min, or ≤24g / 10min, or ≤22g / 10min, or ≤20g / 10min, or ≤18g / 10min, or ≤16g / 10min, or ≤14g / 10min, or ≤12g / 10min, or ≤10g / 10min, or ≤9.0g / 10min, or ≤8.0g / 10min, or ≤7.0g / 10min, or ≤6.0g / 10min, or ≤5.0g / 10min.
[0102] B2] The composition according to any one of A]-A2] above, wherein the molecular weight distribution (MWD = Mw / Mn) of the at least one ethylene / α-olefin multiblock interpolymer (component a) is ≥1.5, or ≥1.6, or ≥1.7, or ≥1.8, or ≥1.9, or ≥2.0 And / or ≤4.0, or ≤3.5, or ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4.
[0103] C2] The composition according to any one of A]-B2] above, wherein the number average molecular weight (Mn) of the at least one ethylene / α-olefin multiblock interpolymer (component a) is ≥10,000 g / mol, or ≥15,000 g / mol, or ≥20,000 g / mol, or ≥25,000 g / mol, or ≥30,000 g / mol, or ≥32,000 g / mol, or ≥35,000 g / mol And / or ≤100,000 g / mol, or ≤90,000 g / mol, or ≤80,000 g / mol, or ≤75,000 g / mol, or ≤70,000 g / mol, or ≤65,000 g / mol, or ≤60,000 g / mol.
[0104] D2] The composition according to any one of A]-C2] above, wherein the melting point (Tm) of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is ≥80°C, or ≥90°C, or ≥100°C, or ≥105°C, or ≥110°C, or ≥112°C, or ≥114°C, or ≥116°C, or ≥118°C as determined by DSC. And / or ≤150℃, or ≤145℃, or ≤140℃, or ≤135℃, or ≤130℃, or ≤128℃, or ≤126℃, or ≤124℃, or ≤123℃, or ≤122℃.
[0105] E2] The composition according to any one of A]-D2] above, wherein the glass transition temperature (Tg) of the at least one ethylene / α-olefin multiblock interpolymer (component a) is ≥-75.0℃, or ≥-72.0℃, or ≥-70.0℃, or ≥-68.0℃, or ≥-66.0℃, or ≥-65.0℃ as determined by DSC. And / or ≤-40.0℃, ≤-45.0℃, ≤-50.0℃, or ≤-55.0℃, or ≤-60.0℃.
[0106] F2] The composition according to any one of A]-E2] above, wherein component a comprises only one ethylene / α-olefin multiblock interpolymer, and further comprises an ethylene / α-olefin multiblock copolymer.
[0107] G2] The composition according to any one of A]-E2] above, wherein component a comprises two ethylene / α-olefin multiblock interpolymers, and further comprises two ethylene / α-olefin multiblock copolymers.
[0108] A3] The composition according to any one of A]-G2] above, wherein the first composition further comprises at least one ethylene / α-olefin interpolymer as component c, and further at least one ethylene / α-olefin copolymer.
[0109] B3] According to the composition described in A3 above, the α-olefin of the at least one ethylene / α-olefin interpolymer and the further copolymer is a C3-C20 α-olefin, and further is a C3-C10 α-olefin, and further is a C3-C8 α-olefin.
[0110] C3] According to the composition described in A3] or B3] above, the α-olefin of the at least one ethylene / α-olefin interpolymer and further copolymer is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further is propylene, 1-butene or 1-octene, and further is propylene or 1-octene, and further is 1-octene.
[0111] D3] The composition according to any one of A3]-C3] above, wherein the density of the at least one ethylene / α-olefin interpolymer (of component c) is ≥0.860 g / cc, or ≥0.862 g / cc, or ≥0.864 g / cc, or ≥0.866 g / cc, or ≥0.868 g / cc, or ≥0.869 g / cc, or ≥0.870 g / cc, And / or ≤0.900g / cc, ≤0.898g / cc, or ≤0.895g / cc, or ≤0.892g / cc, or ≤0.890g / cc, or ≤0.888g / cc, or ≤0.885g / cc, or ≤0.882g / cc, or ≤0.880g / cc, or ≤0.878g / cc, or ≤0.876g / cc, or ≤0.874g / cc, or ≤0.872g / cc.
[0112] E3] The composition according to any one of A3]-D3] above, wherein the melt index (MI or I2) of the at least one ethylene / α-olefin interpolymer (component c) is ≥0.10 g / 10 min, or ≥0.20 g / 10 min, or ≥0.30 g / 10 min, or ≥0.40 g / 10 min, or ≥0.50 g / 10 min, And / or ≤50g / 10min, or ≤45g / 10min, or ≤40g / 10min, or ≤35g / 10min, or ≤30g / 10min, or ≤28g / 10min, or ≤26g / 10min, or ≤24g / 10min, or ≤22g / 10min, or ≤20g / 10min, or ≤18g / 10min, or ≤16g / 10min, or ≤14g / 10min, or ≤12g / 10min, or ≤10g / 10min, or ≤9.0g / 10min, or ≤8.0g / 10min, or ≤6.0g / 10min, or ≤5.0g / 10min, or ≤4.0g / 10min, or ≤2.0g / 10min, or ≤1.0g / 10min.
[0113] F3] The composition according to any one of A3]-E3] above, wherein the molecular weight distribution (MWD = Mw / Mn) of the at least one ethylene / α-olefin interpolymer (component c) is ≥1.5, or ≥1.6, or ≥1.7, or ≥1.8, or ≥1.9, or ≥2.0 And / or ≤4.0, or ≤3.5, or ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4.
[0114] G3] The composition according to any one of A3]-F3] above, wherein the melting point (Tm) of the at least one ethylene / α-olefin interpolymer (component c) as determined by DSC is ≥90°C, or ≥100°C, or ≥105°C, or ≥110°C, or ≥112°C, or ≥114°C, or ≥116°C, or ≥118°C. And / or ≤140℃, or ≤135℃, or ≤130℃, or ≤128℃, or ≤126℃, or ≤124℃, or ≤123℃.
[0115] H3] The composition according to any one of A3]-G3] above, wherein the at least one ethylene / α-olefin interpolymer (of component c) is a multi-block ethylene / α-olefin interpolymer or a random ethylene / α-olefin.
[0116] I3] The composition according to any one of A3]-H3] above, wherein component c comprises only one ethylene / α-olefin interpolymer, and further an ethylene / α-olefin copolymer.
[0117] J3] The composition according to any one of A3]-H3] above, wherein component c comprises two ethylene / α-olefin interpolymers, and further two ethylene / α-olefin copolymers.
[0118] K3] The composition according to any one of A3]-J3] above, wherein the ratio of I2 of component a to I2 of component c is ≥2.0, or ≥4.0, or ≥6.0, or ≥8.0, or ≥9.0, or ≥10 g / 10 min And / or ≤20, or ≤18, or ≤16, or ≤14, or ≤12.
[0119] L3] The composition according to any one of A3]-K3] above, wherein the ratio of the density of component a to the density of component c is ≥0.900, or ≥0.920, or ≥0.950, or ≥0.980, or ≥1.00, or ≥0.101 And / or ≤1.20, or ≤1.15, or ≤1.12, or ≤1.10, or ≤1.08, or ≤1.05, or ≤1.02.
[0120] M3] The composition according to any one of A3]-L3] above, wherein the weight ratio of component a to component c is ≥1.2, or ≥1.5, or ≥1.8, or ≥2.0, or ≥2.2, or ≥2.4. And / or ≤4.0, or ≤3.8, or ≤3.5, or ≤3.2, or ≤3.0, or ≤2.8, or ≤2.6.
[0121] N3] The composition according to any one of A]-M3] above, wherein the first composition further comprises an antistatic agent.
[0122] O3] The composition according to any one of A]-N3] above, wherein the first composition further comprises a nucleating agent.
[0123] [P3] The composition according to any one of [A]-[O3] above, wherein the weight ratio of component b to component a is ≥1.1, or ≥1.2, or ≥1.4, or ≥1.6, or ≥1.8. And / or ≤6.0, or ≤5.8, or ≤5.5, or ≤5.2, or ≤5.0, or ≤4.8, or ≤4.5, or ≤4.2, or ≤4.0, or ≤3.8, or ≤3.5, or ≤3.2, or ≤3.0, or ≤2.8, or ≤2.6, or ≤2.5.
[0124] Q3] The composition according to any one of A]-P3] above, wherein the ratio of the MFR of component b to the I2 of component a is ≥5.0, or ≥6.0, or ≥7.0, or ≥8.0, or ≥9.0, or ≥10, or ≥11, or ≥12. And / or ≤24, or ≤22, or ≤20, or ≤18, or ≤16, or ≤14.
[0125] R3] The composition according to any one of A]-Q3] above, wherein the ratio of the density of component b to the density of component a is ≥0.98, or ≥0.99, or ≥1.00, or ≥1.01. And / or ≤1.20, or ≤1.18, or ≤1.15, or ≤1.12, or ≤1.10, or ≤1.08, or ≤1.06, or ≤1.05, or ≤1.04.
[0126] S3] The composition according to any one of A]-R3] above, wherein, based on the weight of the first composition, the first composition comprises component a ≥ 10% by weight, or ≥ 12% by weight, or ≥ 15% by weight, or ≥ 18% by weight, or ≥ 20% by weight, or ≥ 22% by weight, or ≥ 25% by weight. And / or ≤50% by weight, or ≤48% by weight, or ≤45% by weight, or ≤42% by weight, or ≤40% by weight, or ≤38% by weight, or ≤36% by weight.
[0127] [T3] The composition according to any one of A]-S3] above, wherein, based on the weight of the first composition, the first composition comprises component b ≥ 50% by weight, or ≥ 52% by weight, or ≥ 54% by weight, or ≥ 56% by weight, or ≥ 58% by weight, or ≥ 60% by weight, or ≥ 62% by weight. And / or ≤80% by weight, or ≤78% by weight, or ≤75% by weight, or ≤72% by weight, or ≤70% by weight, or ≤68% by weight, or ≤66% by weight.
[0128] U3] The composition according to any one of A]-T3] above, wherein, based on the total weight of components a and b, the first composition contains component a ≥ 15% by weight, or ≥ 18% by weight, or ≥ 20% by weight, or ≥ 22% by weight, or ≥ 24% by weight, or ≥ 26% by weight, or ≥ 28% by weight. And / or ≤50% by weight, or ≤48% by weight, or ≤45% by weight, or ≤42% by weight, or ≤40% by weight, or ≤38% by weight, or ≤36% by weight.
[0129] V3] The composition according to any one of A3]-U3] above, wherein, based on the weight of the first composition, the first composition comprises component c ≥ 0.50 wt%, or ≥ 1.0 wt%, or ≥ 2.0 wt%, or ≥ 4.0 wt%, or ≥ 6.0 wt%, or ≥ 8.0 wt%, or ≥ 9.0 wt%, or ≥ 10 wt%. And / or ≤30% by weight, or ≤28% by weight, or ≤25% by weight, or ≤22% by weight, or ≤20% by weight, or ≤18% by weight, or ≤16% by weight, or ≤14% by weight, or ≤12% by weight.
[0130] W3] The composition according to any one of A]-V3] above, wherein, based on the weight of the first composition, the sum of components a and b contained in the first composition is ≥70% by weight, or ≥72% by weight, or ≥75% by weight, or ≥78% by weight, or ≥80% by weight, or ≥82% by weight, or ≥84% by weight, or ≥86% by weight, or ≥88% by weight. And / or ≤100% by weight, or ≤99% by weight.
[0131] [X3] The composition according to any one of A3]-W3] above, wherein, based on the weight of the first composition, the sum of components a, b and c contained in the first composition is ≥80% by weight, or ≥82% by weight, or ≥85% by weight, or ≥88% by weight, or ≥90% by weight, or ≥92% by weight, or ≥94% by weight, or ≥96% by weight. And / or ≤100% by weight, or ≤99% by weight.
[0132] Y3] The composition according to any one of A3]-X3] above, wherein the weight ratio of component b to component c is ≥1.0, or ≥1.5, or ≥2.0, or ≥2.5, or ≥3.0, or ≥4.0, or ≥4.5, or ≥5.0, or ≥5.2, or ≥5.4, or ≥5.6, or ≥5.8 And / or ≤10, or ≤9.5, or ≤9.0, or ≤8.5, or ≤8.0, or ≤7.5, or ≤7.0, or ≤6.8, or ≤6.6, or ≤6.4, or ≤6.2.
[0133] Z3] The composition according to any one of A]-G2], N3]-U3] or W3] above, wherein the first composition comprises components a and b as the only polymer components of the first composition.
[0134] A4] The composition according to any one of A3]-Y3] above, wherein the first composition comprises components a, b and c as the only polymer components of the first composition.
[0135] B4] The composition according to any one of A]-A4] above, wherein the composition further comprises at least one filler.
[0136] C4] According to the composition described in B4 above, wherein the at least one filler is selected from talc, nano-clay or a combination thereof, and is further selected from talc.
[0137] D4] The composition according to B4] or C4] above, wherein, based on the weight of the composition, the composition comprises ≥0.50% by weight, or 1.0% by weight, or ≥2.0% by weight, or ≥3.0% by weight, or ≥4.0% by weight, or ≥5.0% by weight. And / or ≤40% by weight, or ≤35% by weight, or ≤30% by weight, or ≤25% by weight, or ≤20% by weight, or ≤15% by weight, or ≤10% by weight, or ≤8.0% by weight, or ≤6.0% by weight.
[0138] E4] The composition according to any one of A]-D4] above, wherein the composition further comprises at least one additive.
[0139] F4] According to the composition described in E4 above, wherein the at least one additive is selected from antioxidants, colorants, processing aids (e.g., zinc stearate), lubricants, or any combination thereof, and is further selected from antioxidants.
[0140] G4] According to the composition described in E4] or F4] above, wherein, based on the weight of the composition, the at least one additive is in the form of ≥0.01% by weight, or ≥0.02% by weight, or ≥0.05% by weight, or ≥0.10% by weight, or ≥0.20% by weight, or ≥0.30% by weight. And / or The amount present is ≤10% by weight, or ≤5.0% by weight, or ≤2.0% by weight, or ≤1.0% by weight, or ≤0.8% by weight, or ≤0.6% by weight.
[0141] H4] A composition according to any one of A]-G4] above, wherein the composition further comprises a polymer that is independently different from each of components a and b in one or more characteristics (such as monomer type, monomer distribution, monomer amount, density, melt index (I2) or melt flow rate (MFR), Mn, MWD or any combination thereof), and further in one or more characteristics (such as monomer type, monomer distribution, monomer amount, density, melt index (I2) or melt flow rate (MFR) or any combination thereof).
[0142] I4] The composition according to any one of A]-H4] above, wherein, based on the weight of the composition, the composition comprises component b ≥ 40% by weight, or ≥ 42% by weight, or ≥ 45% by weight, or ≥ 48% by weight, or ≥ 50% by weight, or ≥ 52% by weight, or ≥ 54% by weight, or ≥ 56% by weight, or ≥ 58% by weight. And / or ≤90% by weight, or ≤88% by weight, or ≤85% by weight, or ≤82% by weight, or ≤80% by weight, or ≤78% by weight, or ≤75% by weight, or ≤72% by weight, or ≤70% by weight, or ≤68% by weight, or ≤66% by weight.
[0143] J4] The composition according to any one of A]-I4] above, wherein, based on the weight of the composition, the composition comprises component a ≤50% by weight, or ≤48% by weight, or ≤45% by weight, or ≤42% by weight, or ≤40% by weight, or ≤38% by weight, or ≤36% by weight. And / or ≥5.0% by weight, or ≥8.0% by weight, or ≥10% by weight, or ≥12% by weight, or ≥15% by weight, or ≥18% by weight, or ≥20% by weight, or ≥22% by weight, or ≥24% by weight.
[0144] [K4] The composition according to any one of A]-J4] above, wherein, based on the weight of the composition, the total of components a and b contained in the composition is ≥60% by weight, or ≥65% by weight, ≥70% by weight, or ≥72% by weight, or ≥74% by weight, or ≥76% by weight, or ≥78% by weight, or ≥80% by weight, or ≥82% by weight, or ≥84% by weight. And / or ≤100% by weight, or ≤99% by weight.
[0145] L4] The composition according to any one of A3]-Y3] or A4]-K4] above, wherein, based on the weight of the composition, the composition comprises component c ≤ 30 wt%, or ≤ 28 wt%, or ≤ 25 wt%, or ≤ 22 wt%, or ≤ 20 wt%, or ≤ 18 wt%, or ≤ 16 wt%, or ≤ 14 wt%, or ≤ 12 wt%. And / or≥0.5% by weight, or ≥1.0% by weight, or ≥2.0% by weight, or ≥4.0% by weight, or ≥6.0% by weight, or ≥8.0% by weight, or ≥9.0% by weight, or ≥10% by weight.
[0146] M4] The composition according to A3]-Y3] or A4]-L4] above, wherein, based on the weight of the composition, the total of components a, b and c contained in the composition is ≥70% by weight, or ≥72% by weight, or ≥75% by weight, or ≥78% by weight, or ≥80% by weight, or ≥82% by weight, or ≥84% by weight, or ≥86% by weight, or ≥88% by weight, or ≥90% by weight, or ≥92% by weight, or ≥93% by weight, or ≥94% by weight. And / or ≤100% by weight, or ≤99% by weight, or ≤98% by weight, or ≤97% by weight, or ≤96% by weight, or ≤95% by weight.
[0147] [N4] The composition according to any one of A]-M4] above, wherein, based on the weight of the composition, the composition comprises ≥70% by weight, or ≥72% by weight, ≥75% by weight, or ≥78% by weight, or ≥80% by weight, or ≥82% by weight, or ≥84% by weight, or ≥86% by weight, or ≥88% by weight, or ≥90% by weight, or ≥92% by weight, or ≥93% by weight, or ≥94% by weight. And / or ≤100% by weight, or ≤99% by weight.
[0148] O4] The composition according to any one of A]-N4] above, wherein, based on the weight of the composition, the composition contains ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of an amide compound (e.g., aliphatic amide); and further, the composition does not contain an amide compound.
[0149] [P4] The composition according to any one of A]-O4] above, wherein, based on the weight of the composition, the composition contains ≤5.0% by weight, or ≤2.0% by weight, or ≤1.0% by weight, or ≤0.5% by weight, or ≤0.2% by weight, or ≤0.1% by weight, or ≤0.05% by weight of polyamide; and further, the composition does not contain polyamide.
[0150] Q4] The composition according to any one of A]-P4] above, wherein, based on the weight of the composition, the composition comprises ≤5.0% by weight, or ≤2.0% by weight, or ≤1.0% by weight, or ≤0.5% by weight, or ≤0.2% by weight, or ≤0.1% by weight, or ≤0.05% by weight of ethylene-vinyl acetate (EVA) polymer; and further, the composition does not contain ethylene-vinyl acetate (EVA) polymer.
[0151] R4] The composition according to any one of A]-Q4] above, wherein the composition comprises ≤5.0% by weight, or ≤2.0% by weight, or ≤1.0% by weight, or ≤0.5% by weight, or ≤0.2% by weight, or ≤0.1% by weight, or ≤0.05% by weight of a metal hydroxide (e.g., magnesium hydroxide); and further, the composition does not contain a metal hydroxide.
[0152] S4] The composition according to any one of A]-R4] above, wherein the composition comprises ≤5.0% by weight, or ≤2.0% by weight, or ≤1.0% by weight, or ≤0.5% by weight, or ≤0.2% by weight, or ≤0.1% by weight, or ≤0.05% by weight based on the weight of the composition; and further, the composition does not contain wax.
[0153] T4] The composition according to any one of A]-S4] above, wherein the composition comprises a tackifier in ≤5.0% by weight, or ≤2.0% by weight, or ≤1.0% by weight, or ≤0.5% by weight, or ≤0.2% by weight, or ≤0.1% by weight, or ≤0.05% by weight based on the weight of the composition; and further, the composition does not contain a tackifier.
[0154] U4] The composition according to any one of A]-T4] above, wherein the MFR of the composition is ≥5.0 g / 10 min, or ≥7.0 g / 10 min, or ≥10 g / 10 min, or ≥12 g / 10 min, or ≥15 g / 10 min, or ≥18 g / 10 min, or ≥20 g / 10 min, or ≥22 g / 10 min, or ≥24 g / 10 min, or ≥26 g / 10 min And / or ≤100g / 10min, or ≤80g / 10min, or ≤60g / 10min, or ≤50g / 10min, or ≤48g / 10min, or ≤45g / 10min, or ≤42g / 10min, or ≤40g / 10min, or ≤38g / 10min, or ≤36g / 10min, or ≤34g / 10min, or ≤32g / 10min.
[0155] V4] The composition according to any one of A]-U4] above, wherein the light transmittance (3.2 mm thickness) of the composition at room temperature (23°C) is ≥30%, or ≥35%, or ≥40%, or ≥45%, or ≥50%, or ≥55%, or ≥60%. And / or The ≤100%, or ≤95%. Transmittance was measured as described in this article.
[0156] W4] The composition according to any one of A]-V4] above, wherein the composition has a dart-drop elongation at -30°C (6.6 m / s) of ≥70%, or ≥75%, or ≥80%, or ≥85%, or ≥90%, or ≥95%, or 100%. The dart-drop elongation is determined as described herein.
[0157] [X4] The composition according to any one of A]-W4] above, wherein the composition has a Charpy impact at 23°C (room temperature) of ≥400 J / m, or ≥410 J / m, or ≥420 J / m, or ≥430 J / m, or ≥440 J / m, or ≥450 J / m, or ≥460 J / m, or ≥470 J / m, or ≥480 J / m, or ≥490 J / m, or ≥500 J / m. The Charpy impact is determined as described herein.
[0158] [Y4] The composition according to any one of A]-X4] above, wherein the composition has a Charpy impact at -30°C ≥40 J / m, or ≥41 J / m, or ≥42 J / m, or ≥43 J / m, or ≥44 J / m, or ≥45 J / m, or ≥46 J / m, or ≥47 J / m, or ≥48 J / m, or ≥49 J / m. The Charpy impact is determined as described herein.
[0159] Z4] The composition according to any one of A]-Y4] above, wherein the flexural modulus of the composition is ≥80 ksi, or ≥85 ksi, or ≥90 ksi, or ≥95 ksi, or ≥100 ksi, or ≥105 ksi, or ≥110 ksi. The flexural modulus is determined as described herein.
[0160] A5] An article comprising at least one component formed from any one of the compositions described in A]-Z4 above.
[0161] B5] The article described in A5 above, wherein the article is an automotive part.
[0162] C5] The article according to A5] or B5] above, wherein the article is a bumper or an inner door panel, and more particularly a bumper.
[0163] D5] A method of forming an article, the method comprising mixing the composition described in any one of A]-Z4 above.
[0164] [E5] According to the method described in [D5] above, the method further includes heat treating the composition.
[0165] F5] According to the method described in D5] or E5] above, the article is an automotive part.
[0166] G5] According to any one of D5]-F5] above, the article is a bumper or an inner door panel, and more particularly a bumper.
[0167] Test methods
[0168] Melt flow rate of propylene-based polymers or polymer compositions
[0169] Melt flow rate (MFR) for propylene-based polymers (see Table 1) or compositions (see Table 2) was measured according to ASTM D-1238, at 230°C / 2.16 kg. Melt index (MI or I2) for ethylene-based polymers or compositions was measured according to ASTM D-1238, at 190°C / 2.16 kg.
[0170] density
[0171] The polymer density was measured according to ASTM D792, using a non-annealed testing setup (the annealing step was skipped), employing a balance and an isopropanol bath. Each sample was first compressed at 190°C and 3000 lbs for 6 minutes, then compressed at 25000 lbs for 4 minutes, followed by cooling at 15°C / min until the sample reached 30°C. After compression molding, the density of the polymer sample was measured within 1 hour in an isopropanol bath (temperature controlled at 23°C ± 0.2°C). Results are expressed in grams per cubic centimeter (g / cc = g / cm³). 3 )Record.
[0172] Differential scanning calorimetry (DSC) and SS-Tm determination for ethylene / α-olefin multiblock interpolymers (POE)
[0173] Differential scanning calorimetry (DSC) can be used to measure the melting, crystallization, and glass transition behavior of polymers over a wide temperature range. For example, this analysis can be performed using the TA Discovery DSC instrument equipped with a refrigerated cooling system (RCS) and an autosampler. During testing, a nitrogen purge gas flow of 50 ml / min is used. Each sample is melt-pressed into a thin film at approximately 190°C (preheated for 2 minutes and pressed at 10 MPa for 2 minutes). The molten sample is then air-cooled to room temperature (approximately 23–25°C). Samples of 6 mm diameter (3–10 mg) are removed from the cooled polymer, weighed, placed in a light aluminum pan (approximately 50 mg), and sealed. Analysis is then performed to determine its thermal properties.
[0174] The thermal behavior of the sample was determined by generating a heat flow versus temperature curve through steep inclines and declines in the sample temperature. First, for POE, the sample was rapidly heated to 180°C and held isothermally for 5 minutes to remove its thermal history. Next, the sample was cooled to -90°C at a cooling rate of 10°C / min and held isothermally at -90°C for 5 minutes. Then, for POE, the sample was heated to 180°C at a heating rate of 10°C / min (this is the "second heating" rise). The cooling and second heating curves were recorded.
[0175] Glass transition temperature T g The liquid heat capacity of half of the samples was determined by the second heating curves of DSC, as described in Bernhard Wunderlich, The Basis of Thermal Analysis, Thermal Characterization of Polymeric Materials, 92, 278–279 (Edith A. Turi, 2nd ed., 1997). Baselines were plotted above and below the glass transition region and passed through T... g The baseline is extrapolated from the region. The sample heat capacity at the temperature between these baselines is T. g The melting point T of the polymer sample m The temperature corresponding to the maximum heat flux (endothermic peak) in the second DSC heating curve was determined. The crystallization temperature of the polymer sample was determined to be the temperature corresponding to the maximum exothermic temperature in the DSC cooling curve (or the temperature corresponding to the lowest drop of the exothermic peak at the crystallization peak (peak temperature)). The percentage of crystallinity was determined by the heat of fusion (H₂O) determined by the second heating curve. f Divide the crystallinity by the theoretical heat of fusion (e.g., 292 J / g for ethylene-based polymer samples) and multiply that amount by 100 to calculate (e.g., for ethylene-based polymer samples, crystallinity % = (H) f (292J / g)×100).
[0176] At a specific temperature (T) s The cumulative crystallinity at T is calculated by first determining the sample's crystallinity at T. s Heat of fusion between 140°C and H s This is determined by [the following]. In this case, the second heating curve is baseline corrected by drawing a linear baseline between the heat flow at -50°C and 140°C. The baseline can then be determined from the two temperature points (i.e., T). s The heat flux curve calculated using the integral baseline correction between H and 140℃ was used to determine H. s Then by using H s Divide by the theoretical heat of molten PE, 292 J / g, and multiply that by 100 to calculate the specific temperature (T). s The cumulative crystallinity at T (e.g., % cumulative crystallinity at T) s (location) = (H) s / 292J / g)×100 (for PE)). Then the change in crystallinity of POE between room temperature and 60°C is calculated as the crystallinity change at T s =23℃ cumulative crystallinity and at T s = The difference in cumulative crystallinity at 60℃.
[0177] The melting temperature of the soft segment, SS-Tm, is determined by the second heating curve of DSC. For example, ethylene / octene multiblock copolymers typically have two melting peaks: one associated with the soft segment and one associated with the hard segment. SS-Tm is associated with the lower temperature peak of the soft segment. For some block copolymers, the peak associated with the melting of the soft segment is a small peak (or a bulge) on the baseline, making it difficult to assign the maximum peak value. This difficulty can be overcome by converting the ordinary DSC curve into a weighted DSC curve using the following method.
[0178] In DSC, heat flux depends on the amount of material melting at a given temperature and the temperature-dependent specific heat capacity. The temperature dependence of the specific heat capacity in the molten state of linear low-density polyethylene (LDPE) leads to an increase in heat of fusion as the comonomer content decreases. That is, as the comonomer content increases, crystallinity decreases, and the heat of fusion gradually decreases. See Wild, L., Chang, S., Shankernarayanan, M J., Improved Method for Compositional Analysis of Polyolefins by DSC, Polym. Prep 1990; 31: 270-1, which is incorporated herein by reference in its entirety. For a given point in the DSC curve (defined by heat flux in watts per gram (W / g) and temperature in degrees Celsius), the DSC curve can be converted into a weight-dependent distribution curve by taking the ratio of the temperature-dependent heat of fusion (ΔH(T)) to the expected heat of fusion of the linear copolymer, as discussed below.
[0179] For DSC analysis of the composition, baseline correction is performed on the second heating curve, for example, by plotting a linear baseline between the heat fluxes at -50°C and 135°C. The temperature-dependent heat of fusion (or enthalpy (J / g) versus temperature (°C)) can then be generated from the sum of the integrated heat fluxes between two consecutive data points (from the "Heat Flux (W / g) vs. Time (min)" curve). This sum is generally represented by the cumulative enthalpy curve ("Enthalpy (J / g) vs. Temperature (°C)" curve). Note that Joules (J) = Watts (W) * seconds, and each temperature is determined by the corresponding time point and temperature ramp.
[0180] The expected relationship between the heat of fusion of linear ethylene / octene copolymers at a given temperature is shown by the "Heat of fusion vs. Melting Temperature" curve. Using atactic ethylene / octene copolymers, the expected heat of fusion ΔH of the linear copolymers can be obtained. 线性共聚物 The following relationship (calibration equation) is established between the melting temperature Tm (in °C): See also Figure 2 ("Enthalpy of melting (J / g) and melting temperature (°C) of linear copolymers").
[0181] For each integral data point from the cumulative enthalpy curve (“enthalpy (J / g) vs. temperature (°C)” curve) at a given temperature (T), the ratio of “enthalpy from the cumulative enthalpy curve to the expected heat of fusion of the linear copolymer at that temperature” produces a fractional weight that can be assigned to the corresponding data point. Therefore, DSC weight fraction = [cumulative enthalpy (at T) from the calibration equation / enthalpy of fusion (at T)]. Using this ratio, a curve of DSC weight fraction versus temperature (°C) can be generated, and the area under that curve (or A) can be calculated.总和 This can be achieved by dividing the DSC weight fraction by A. 总和 (or DSC weight fraction / A) 总和 The normalized DSC weight fraction at each temperature (T) is calculated. This generates a normalized DSC weight fraction versus temperature (°C) curve. The soft segment Tm (SS-Tm) is specified as the temperature at which the maximum value is located in the normalized DSC weight fraction versus temperature (°C) curve. This method is applicable to copolymers containing polymerized ethylene and polymerized octene, but can also be applied to other polymers. Note that the above DSC method can be used to determine the T values of ethylene / α-olefin interpolymers and copolymers. m T g and T c .
[0182] Differential Scanning Calorimetry (DSC) – Polymer-Based on PP
[0183] As discussed below, differential scanning calorimetry (DSC) is used to measure T in propylene (PP)-based samples. m T c T g Crystallinity. Each sample (0.5 g) was compressed and molded into a film at 25000 psi and 190 °C for 10-15 seconds. Approximately 5 mg to 8 mg of the film sample was weighed and placed in a DSC pan. The lid was screwed on the pan to ensure a closed atmosphere. The sample pan was placed in the DSC cell, and for PP, it was heated to a temperature of 230 °C at a rate of approximately 10 °C / min. The sample was held at this temperature for three minutes. Then, for PP, the sample was cooled to -80 °C at a rate of 10 °C / min and held isothermally at this temperature for three minutes. The sample was then heated at a rate of 10 °C / min until completely melted (second heating). Unless otherwise specified, the melting point (T) of each polymer sample is... m ) and glass transition temperature (T g The crystallization temperature (T) was determined by the second heating curve and the crystallization temperature (T) was determined by the second heating curve. c The temperature (T) is determined by the first cooling profile. Record T. g , and T m The corresponding peak temperature. For PP, the percentage of crystallinity can be determined by taking the heat of melt (H) determined by the second heating curve. f Divide by the theoretical heat of fusion, 165 J / g, and multiply that amount by 100 to calculate (e.g., crystallinity % = ((Hf / 165 J / g) × 100 (for PP)).
[0184] Displaced Charpy, J / m (-30℃ and 23℃ (room temperature))
[0185] This test, based on ISO 179, determines Charpy impact performance by calculating the impact energy absorbed by the specimen after automatic determination of wind resistance and frictional losses. Ten test specimens were die-cut from 4 mm thick ISO injection-molded rods (see Experimental Section). Each specimen was 80 mm long and 10 mm wide. An automatic notch was used to cut each specimen along its length at the center in the thickness direction. Each specimen was conditioned for at least 40 hours at 23 ± 2 °C and 50 ± 10% relative humidity. For those specimens tested at non-ambient temperatures (i.e., -30 °C), each specimen was further conditioned for at least one hour at the test temperature. For each test temperature, ten specimens (each composition) were tested, and the average Charpy value was reported.
[0186] Flexural modulus
[0187] Flexural modulus was measured according to ISO 178 using an injection-molded ISO tensile bar (see Experimental Section) and an INSTRON testing machine. The testing speed was 2 mm / min. Five test samples (for each composition) were measured, and the average value was recorded. The tangential modulus of elasticity described in ISO 178 is reported as the flexural modulus of the composition.
[0188] Multi-axis dart impact (dart extension)
[0189] According to ASTM D3763, multiaxial dart tests were performed on each composition using an INSTRON CEAST 9350 drop hammer impact system (DYNATUP). The tests were conducted at a speed of 6.6 m / s, equivalent to 14.8 mph, which is the automotive industry standard rate. Sample temperature was carefully controlled. The samples (TPO discs, see Experiments section) were placed in a freezing unit for at least four hours, which maintained the test temperature at + / - 2°C. The impact tests were conducted in a temperature-controlled chamber, which maintained the test temperature at + / - 2°C. In this case, the test samples were tested at -30°C. The samples (3.2 mm thick discs) may fracture in a ductile, semi-brittle, or brittle mode. The mode was determined by visual inspection of the impacted disc. Note that the impact on the disc created a hole in the center of the disc. The semi-brittle (C) sample had a crack in addition to the central hole but no missing pieces (score 0.5). Brittle (B) samples have missing pieces from the disk (score 0), which typically occurs in the central region of the disk, thus obscuring the outline of the central hole. Ductile (D) samples have only one hole in the center of the disk (score 1). The ductility % of each composition is calculated by dividing the total score of each batch of tests by the total number of samples in that batch (at least 5), and then multiplying by 100.
[0190] transmittance %
[0191] The transmittance of each composition was measured using a Haze-Gard Plus (BYK Instruments) according to ASTM D1003 from a 3.2 mm thick injection-molded disk (TPO disk, see Experimental Section). This method measures transmittance as the ratio of luminous flux passing through the object to the flux incident on the object. The reported value is the percentage (%) of the transmitted flux (light). For transmittance at room temperature (23°C), no pre-sample treatment was required for measurement. For each composition, the transmittance obtained at each temperature was the average of at least three (typically 3 to 5) independent measurements.
[0192] Gel permeation chromatography for propylene-based polymers
[0193] The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high-temperature GPC chromatograph equipped with an internal IR5 infrared detector. The autosampler oven zone was set at 160°C, and the column oven zone at 140°C. The columns were three AGILENT "Mixed B" 30cm, 10µm linear mixed-bed columns. The chromatographic solvent was 1,2,4-trichlorobenzene containing 200ppm of butylated hydroxytoluene (BHT). The solvent source was bubbled with nitrogen. The injection volume was 200µL, and the flow rate was 1.0mL / min.
[0194] The calibration of the GPC column assembly was performed using 21 narrow molecular weight distribution polystyrene (PS) standards, ranging from 580 to 8,400,000, arranged in a six-cocktail mixture, with each molecular weight separated by at least one order of magnitude. These standards were purchased from Agilent Technologies. For polystyrene standards with a molecular weight equal to or greater than 1,000,000, 0.025 g was dissolved in 50 mL of solvent; for polystyrene standards with a molecular weight less than 1,000,000, 0.05 g was dissolved in 50 mL of solvent. The polystyrene standards were pre-dissolved by gentle stirring at 80°C for 30 min, then cooled, and the room-temperature solution was transferred to an autosampler dissolution oven at 160°C and held for 30 min. The peak molecular weights of the polystyrene standards were converted to polypropylene (PP) molecular weights using Equation 1 (as described in ASTM D6474):
[0195] (Equation 1)
[0196] Where M is the molecular weight, K PS It is 0.0019 mL / g, α PS K is 0.655. PP It is 0.0019 mL / g, αPP The value is 0.725. A third-order polynomial is used to fit the corresponding polypropylene equivalent calibration point.
[0197] The total plate number of the GPC column setup was determined using decane, which was introduced into the blank sample via a micropump controlled by a PolymerChar GPC-IR system. For three Agilent “Mixed B” 30 cm, 10 μm linear mixed-bed columns, the plate number of the chromatographic system should be greater than 18,000.
[0198] Samples were prepared semi-automatically using PolymerChar "Instrument Control" software, with a target sample weight of 2 mg / ml. The solvent (containing 200 ppm BHT) was added via a PolymerChar high-temperature autosampler to a pre-bubbled, septum-sealed vial. The sample was dissolved at 160°C for 3 hours with "low-speed" oscillation.
[0199] Mn (GPC) Mw (GPC) and Mz (GPC) The calculations are based on GPC results using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph, according to Equations 2-4 and PolymerChar GPCOne. ™ The software, the IR chromatograms at each equally spaced data acquisition point (i) after deducting the baseline, and the equivalent molecular weight of polypropylene at point (i) obtained from the narrow standard calibration curve of Equation 1.
[0200] (Equation 2),
[0201] (Equation 3),
[0202] (Equation 4).
[0203] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow marker (FM) was used to linearly correct the pump flow rate (nominal flow rate) for each sample by comparing the RV (RV(FM sample)) of the corresponding decane peak within the sample with the RV (RV(FM calibrated)) of the alkane peak within the narrow standard calibration. It was then assumed that any variation in the decane marker peak time was linearly related to the flow rate (effective flow rate) throughout the run. Based on the flow marker peak calibration system, the effective flow rate (relative to the narrow standard calibration) was calculated using Equation 5: The processing of the flow marker peak was performed via PolymerChar GPCOne. ™The software performs the necessary flow correction. Acceptable flow correction ensures that effective flow is within + / - 0.5% of the nominal flow.
[0204] Flow rate (effective) = Flow rate (nominal) * (RV (FM calibrated) / RV (FM sample)) (Equation 5).
[0205] Gel permeation chromatography (GPC) for ethylene-based polymers
[0206] The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high-temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven zone was set at 160°C, and the column oven zone at 150°C. The columns were four Agilent "Mixed A" 30cm 20µm linear mixed-bed columns. The chromatographic solvent was 1,2,4-trichlorobenzene containing 200 ppm of butylated hydroxytoluene (BHT). The solvent source was bubbled with nitrogen. The injection volume was 200 μL, and the flow rate was 1.0 mL / min.
[0207] The calibration of the GPC column was performed using 21 polystyrene standards with narrow molecular weight distributions, ranging from 580 to 8,400,000, arranged in a six-component "cocktail" mixture, with each molecular weight separated by at least one order of magnitude. These standards were purchased from Agilent Technologies. For polystyrene standards with a molecular weight equal to or greater than 1,000,000, 0.025 g was dissolved in 50 mL of solvent; for polystyrene standards with a molecular weight less than 1,000,000, 0.05 g was dissolved in 50 mL of solvent. The polystyrene standards were pre-dissolved by gentle stirring at 80°C for 30 min, then cooled, and the room-temperature solution was transferred to an autosampler dissolution oven at 160°C and held for 30 min. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 6 (e.g., Williams and Ward, J. Polym.Sci., Polym.Let., 6, 621 (1968)).
[0208] (Equation 6)
[0209] Where M is the molecular weight, A has a value of 0.4100, and B equals 1.0. A fifth-order polynomial is used to fit the calibration point for the corresponding polyethylene equivalent.
[0210] The total plate number of the GPC column assembly was determined using decane, which was introduced into the blank sample via a micropump controlled by a PolymerChar GPC-IR system. For four Agilent “Mixed A” 30 cm, 20 μm linear mixed-bed columns, the plate number of the chromatographic system should be greater than 18,000.
[0211] Samples were prepared semi-automatically using PolymerChar "Instrument Control" software, with a target sample weight of 2 mg / ml. The solvent (containing 200 ppm BHT) was added via a PolymerChar high-temperature autosampler to a pre-bubbled, septum-sealed vial. The sample was dissolved at 160°C for 3 hours with "low-speed" oscillation.
[0212] Mn (GPC) Mw (GPC) and Mz (GPC) The calculations are based on GPC results using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph, according to equations 7-9 and PolymerChar GPCOne. ™ The software, the IR chromatograms at each equally spaced data acquisition point (i) after deducting the baseline, and the polyethylene equivalent molecular weight at point (i) obtained from the narrow standard calibration curve of Equation 6.
[0213] (Equation 7)
[0214] (Equation 8)
[0215] (Equation 9).
[0216] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow marker (FM) was used to linearly correct the pump flow rate (nominal flow rate) for each sample by comparing the RV (RV(FM sample)) of the corresponding decane peak within the sample with the RV (RV(FM calibrated)) of the alkane peak within the narrow standard calibration. It was then assumed that any variation in the decane marker peak time was linearly related to the flow rate (effective flow rate) throughout the run. Based on the flow marker peak calibration system, the effective flow rate (relative to the narrow standard calibration) was calculated using Equation 10. (Performed via PolymerChar GPCOne) ™ The software processes the flow marker peaks. Acceptable flow correction ensures that the effective flow rate is within + / - 0.5% of the nominal flow rate.
[0217] Flow rate (effective) = Flow rate (nominal) * (RV (FM calibrated) / RV (FM sample)) (Equation 10).
[0218] experiment
[0219] The polymers and additives are shown in Table 1 below. The TPO compositions and their properties are shown in Table 2.
[0220] Table 1: Polymers and Additives
[0221]
[0222] Table 2: TPO Compositions and Properties
[0223]
[0224]
[0225] Mixing
[0226] For each composition (TPO), the components were mixed in a twin-screw extruder; a COPERION ZSK-26mm twin-screw extruder was used, equipped with a water bath and wire cutter. The extruder configuration and temperature profiles for each composition are shown in Table 3. All components except talc were dry-mixed in a plastic bag and then fed into the main feed throat via a loss-in-weight feeder. Talc was fed into the main feed throat via a separate powder feeder.
[0227] Table 3: Blending Conditions
[0228]
[0229] Injection Molding - ISO Stretch Bar
[0230] ISO tensile bars were injection molded on a TOYO injection molding machine. Molding conditions were optimized through various control experiments to ensure minimal defects in the tensile test bar components. Key injection settings are listed in Table 4. ISO tensile bars are used to determine flexural modulus and Charpy impact properties.
[0231] Table 4: Injection Molding Conditions for ISO Tension Bars
[0232]
[0233] Injection Molding - TPO Disk
[0234] TPO discs (4-inch diameter) with a thickness of 1 / 8 inch (3.2 mm) were injection molded on a TOYO injection molding machine. Molding conditions were optimized through various control experiments to ensure minimal defects in the tensile test bar components. Key injection settings are listed in Table 5. The discs were used for light transmittance (%) and dart drop ductility testing.
[0235] Table 5: Injection Molding Settings
[0236]
[0237] Summary of Results
[0238] As shown in Table 2, the compositions of the present invention exhibit good light transmittance, good impact performance (Charpy impact at room temperature and -30°C; dart ductility), and good stiffness (flexural modulus). Compared with the corresponding comparative compositions, each composition of the present invention has improved light transmittance (see Comparative Example A of Invention Example 1 and Comparative Example B of Invention Example 2).
Claims
1. A composition comprising a first composition, the first composition comprising at least the following components a and b: a) at least one ethylene / α-olefin multiblock interpolymer, and b) At least one propylene-based polymer, wherein the MWD of the propylene-based polymer is ≤5.
0.
2. The composition according to claim 1, wherein the MWD of the at least one propylene-based polymer of component b is ≥2.
0.
3. The composition according to claim 1 or 2, wherein the T of the at least one propylene-based polymer of component b m1 ≤160℃.
4. The composition according to any one of claims 1 to 3, wherein the at least one propylene-based polymer of component b has a T m2 And among them (T) m1 – 11.0℃) ≤ T m2 ≤ (T m1 – 5.0℃).
5. The composition according to any one of claims 1 to 4, wherein the at least one propylene-based polymer of component b is a propylene homopolymer.
6. The composition according to any one of claims 1 to 5, wherein component b comprises a propylene-based polymer.
7. The composition according to any one of claims 1 to 6, wherein the density of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is from 0.870 g / cc to 0.910 g / cc.
8. The composition according to any one of claims 1 to 7, wherein the SS-Tm of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is -20°C to 35°C.
9. The composition according to any one of claims 1 to 8, wherein the melt index (MI or I2) of the at least one ethylene / α-olefin multiblock interpolymer (of component a) is from 0.10 g / 10 min to 50 g / 10 min.
10. The composition according to any one of claims 1 to 9, wherein the first composition further comprises at least one ethylene / α-olefin interpolymer as component c.
11. The composition according to claim 10, wherein the weight ratio of component a to component c is 1.2 to 4.
0.
12. The composition according to any one of claims 1 to 11, wherein the weight ratio of component b to component a is 1.1 to 6.
0.
13. The composition according to any one of claims 1 to 12, wherein the composition further comprises at least one filler.
14. The composition according to any one of claims 1 to 13, wherein the MFR of the composition is from 5.0 g / 10 min to 100 g / 10 min.
15. The composition according to any one of claims 1 to 14, wherein the light transmittance (3.2 mm thickness) of the composition at room temperature (23°C) is 30% to 100%.
16. The composition according to any one of claims 1 to 15, wherein the composition has a dart-drop elongation of ≥70% at -30°C (6.6 m / s).
17. The composition according to any one of claims 1 to 16, wherein the composition has a Charpy impact of ≥400 J / m at 23°C (room temperature).
18. The composition according to any one of claims 1 to 17, wherein the flexural modulus of the composition is ≥80 ksi.
19. An article comprising at least one component formed from the composition of any one of claims 1 to 18.
20. A method of forming an article, the method comprising mixing the composition according to any one of claims 1 to 18.
Citation Information
Patent Citations
Illuminated panel assembly
GB2552996A
Painted polyolefin articles
US10557005B2
Vehicular component incorporating concealable indicia with controlled light transmission
US20120313392A1
Illuminated translucent body panels and methods therefor
US20150291085A1
Ethylene interpolymerizations
US5844045A
